تأهيل الموارد البشرية و أثره على المؤسسة الاقتصادية: دراسة حالة وكالة اتصالات الجزائر- الأغواط - علالي خدوجة مارية; تاج رقية; قرادي عبد القادر (جامعة عمار ثليجي -الأغواط, 2022)
This note aimed to identify the impact of human resources qualification on the performance of the economic institution. In order to achieve the objectives of the study, we defined human resource development, as well as rehabilitation in the economic field and the various factors affecting its activities. We also discussed models for improving performance and approaches to modern administrations, as well as administrative empowerment. We discussed the term performance in terms of its concept and the factors affecting it, as well as its determinants and types according to several criteria. We also addressed the performance measurement and evaluation of the performance of the institution as a whole, as well as its indicators. We conducted a field study and conducted an interview with the director of human resources to find out both the number of workers within the agency, as well as the programmed training courses, their time and place, and the knowledge of the relationship between training and employment. key words: Human resources - administrative empowerment - human resources qualification - institution performance - Algeria Telecom - Laghouat Agency.